Development of Emotion Comprehension in Russian Children - Ulyana D. Guseva (Национальный психологический журнал)
Background. Research on the development of emotion comprehension has accumulated a significant body of evidence. However, few studies address the extent to which emotion understanding varies across cultural contexts. This is the first study to compare the development of emotion comprehension in children from Russia, China, and Italy. Objectives. The research aims to compare the development of the ability to understand emotions in Russian children aged 3 to 10 years with previously published diagnostic results for children of similar ages in Italy and China. Study Participants. The sample of our study consisted of 925 children from Russia aged 36 to 119 months (M = 78.4 months; SD = 21.2 months) who attended public preschools and schools in Moscow in 2022–2024. Of these, 456 (49.3%) were boys and 469 (50.7%) were girls. Samples from other studies of emotion understanding in children that were compared with the Russian sample were: 1478 children aged 36 to 131 months from Italy (M = 73.5 months) and 257 children aged 42 to 114 months from China (M = 77.6 months). Methods. To diagnose the ability to understand emotions in preschoolers, the F. Pons’ technique “Test of Emotion Comprehension” (TEC) was used. The assessment of emotion comprehension in children from Russia, Italy and China was carried out using a version of the specified test, adapted in accordance with the language specifics of each group of participants. Results. The study showed that overall emotional understanding scores in Chinese children exceed those of Russian children. The difference between Russian and Italian children is insignificant and is only evident in a certain age range. Russian children demonstrate higher efficiency in recognizing emotions, understanding the nature of hidden emotions, and recognizing the moral component of emotional experiences. While children from Italy and China are more effective in developing the ability to connect emotions with beliefs, desires, and memories, as well as manage their emotional reactions. Conclusions. The results confirm the cultural specificity of emotional development. Russian children are successful in recognizing hidden and moral emotions, but lag behind in understanding the cognitive aspects of emotions. The study highlights the importance of cultural context in studying the understanding of emotions.